Аналоговая обработка сигнала изображения - Атаханов Рашид Маматханович (Фан, 1991)
Экземпляры: КХ (20090205) / Инвентарный номер: 993816 / Цена: / Сис.шифр: 32.94 / Авт.знак: А 92 / ГРНТИ: 19 / ББК: 32.94